Enhancement of flow in pipeline transportation for crude oil emulsion - Khoo, Sue Ann (2012)
This study presents the flow enhancement of crude oil in pipeline transportation using emulsion.High viscosity and low pour point of crude oil often hinder transportation from processing wells to the enhanced oil recovery reservoir. Therefore,a stable oil-in-water emulsion is desired, by comparing different types of surfactant.Demulsification process too is necessary to separate the oil in water. Emulsion was prepared using Span 80,Span 83,and Triton X-100 each respectively in a ratio of 70-30% o/w and 50-50% o/w. Parameters include varying mixing speed in emulsion preparation, temperature and rheological properties of the emulsion were studied by carrying out stability tests. Interfacial properties such as surface tension and interfacial tension of the emulsion were also measured. The effect of droplet diameter with surfactant concentration in the emulsion was also studied.The most stable emulsion was used for transportation in a 3meter pipeline.Rheological data on the emulsion was used to correlate to the laminar flow during transportation.Three demulsifiers: dioctylamine, cocoamine,hexylamine were used to compare for their effectiveness in demulsification.The study reveals that the stability of o/w emulsion increases when an anionic surfactant,Span 83,was used.By increasing the oil content, the speed and mixing temperature resulted in an increased emulsion stability,and a reduced droplet diameter. Dioctylamine proved to be the best demulsifier among cocoamine and hexylamine.